PARENTS’ VIEW OF PRIMARY SCHOOL CHILDREN’S PROGRESS: PRELIMINARY ASSESSMENT OF THE PROGRAM OF SENSORIMOTOR CORRECTION - Levikins, Vadims; Kolesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the study was a preliminary assessment of the sensorimotor correction program based on parental complaints about the difficulties experienced by primary school children and the improvements observed during the program. In most cases, parents are interested in the regular and systematic implementation of the correction program and are among the sources for assessing its results. The study involved 37 mothers with children aged 8 to 11 years (M = 9.8 years; SD = 1.1; 16% girls). Mothers were from 28 to 50 (M = 37.7 years; SD = 6.7). Before the correctional work, each mother was interviewed to identify problems. In the process of sensorimotor correction, one individual lesson was held with the child every week in the presence of a mother. Children performed exercises daily. Mothers received additional sessions every three weeks as part of informational and emotional support. For all identified categories (Self-regulation, Communication, Health and physical development, and Cognitive processes), the improvements after the correction concur with the manifestation of the problem before it. Thus, parents’ assessments of improvements confirm the orientation of the correction to problem areas of children's development.